Teoría sobre la acción de inexistencia del acto administrativo que ha nacido a la vida jurídica por error de la administracion y que causa un grave perjuicio (2016)
The State or public entities expressed through administrative acts, made administrative, administrative operations, in fact, administrative omissions and the administrative silence. But in this research, we will develop the respective to the administrative acts in violation of the fundamental rights. The purpose of this work is to determine that Administration sees as a public entity cometimes it happens that the fundamental rights can be break, specially with their administrative actions, thus it must take into account the principle of supremacy of the Constitution and as a result the particular opportunity to choose the constitutional protection as a way to the immediate protection of fundamental rights.The subject of this study focuses on the regard to causes of non provenance of the tutelage act when it is directed against official decisions but that could obatin the constitutional protection to safeguard the fundamental rights followed by the principle of Constitution supremacy.